E-Procurement and Organizational Performance in the Oil and Gas Industry: The Moderating Role of Technological Capability - Asare, Gabriel (International Journal of Supply Chain and Logistics, 2024)
Purpose: The adoption and utilization of information technologies has a strong impact on organizations performance. E-Procurement process is basically intended to maintain a strategic distance from human interface particularly the provider and purchaser communication amid the pre-bidding stage. This study seeks to examine the moderating role of technological capability on the relationship between E-procurement and organizational performance in oil and gas industry. Methodology: The study adopted a descriptive and exploratory study design. Quantitative approach was adopted to examine and determine the modern phenomenon between the variable: E-procurement, organizational performance and technological capability in the oil and gas industry. Simple random sampling and purposive sampling techniques were used. A sample size of 106 was used. Quantitative data from questionnaires was collected and processed and analyzed using Statistical Package for Social Sciences (SPSS version 25) for accuracy. Factor analysis and structural equation modelling was run to examine the relationship among the study variables set out in the objectives. Findings: Findings show moderately significant relationship between e-procurement and organizational performance in the oil and gas industry, which means that as e-procurement increases, organizational performance is also likely to increase. Furthermore, findings show that there is statistically significant moderate relationship between technological capability and organizational performance in the oil and gas industry. The study concluded that, interaction between technological capability and e-procurement does not significantly influence the strength or direction of the relationship between e-procurement and organizational performance. Unique Contribution to Theory, Policy and Practice: The study recommends that, managers should prioritize developing their technological skills in order to increase organizational performance.